Administration of embryonic stem cell-derived thymic epithelial progenitors expressing MOG induces antigen-specific tolerance and ameliorates experimental autoimmune encephalomyelitis. (April 2015) - Su, Min; Song, Yinhong; He, Zhixu; Hu, Rong; Rood, Debra; Lai, Laijun
Abstract: Tolerance induction, and thus prevention or treatment of autoimmune disease, is not only associated with the persistent presence of self-antigen in the thymus, but also relies on a functional thymus; however, the thymus undergoes profound age-dependent involution. Thymic epithelial cells (TECs) are the major component of the thymic microenvironment for T cell development. We have reported that mouse embryonic stem cells (mESCs) can be induced in vitro to generate thymic epithelial progenitors (TEPs) that further develop into functional TECs in vivo . We show here that transplantation of mESC-TEPs expressing self-antigen myelin oligodendrocyte glycoprotein (MOG) in mice results in enhanced T cell regeneration, long-term expression of MOG in the thymus, prevention of experimental autoimmune encephalomyelitis (EAE) development, and remission of established EAE. Our findings indicate that transplantation of ESC-TEPs expressing disease-causative self-antigen(s) may provide an effective approach for the prevention and treatment of autoimmune disease. Highlights: Transplantation of MOG/mESC-TEPs leads to long-lasting MOG expression in the thymus. MOG/mESC-TEPs in the thymus induces MOG antigen-specific tolerance. Transplantation of MOG/mESC-TEPs in mice prevents EAE development. MOG/mESC-TEPs in mice results in long-term remission of established EAE.